2019
DOI: 10.1002/joa3.12230
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of recurrence after pulmonary vein isolation in patients with normal left atrial diameter

Abstract: Background Enlarged left atrium (LA) is an established predictor of recurrence of atrial fibrillation (AF) after pulmonary vein isolation (PVI), but occasionally recurrences of AF/atrial tachycardia (AT) are experienced in patients with normal left atrial diameter. Therefore, the predictors of AF recurrence and AF triggers were evaluated in patients with normal LA. Methods We enrolled 168 patients with normal LA (<40 mm) who underwent PVI. Various predictors were compared, including age, gender, coronary risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Similar reduction in RA voltage with increased low voltage areas have also been seen in a clinical study involving human patients with long standing PH 25 . Findings from another prospective observational study also suggested that structural RA changes might play a role in AF recurrence in n = 168 AF patients with normal sized LA (defined as diameter < 40 mm) who have undergone a pulmonary vein isolation procedure 26 . In this study by Yano et al, 26 severe tricuspid regurgitation along with a high B‐natriuretic peptide (BNP) were identified as independent predictors of AF recurrence post PVI in this group of AF patients with normal sized LA 26 .…”
Section: Role Of Right Atrial Structural Remodeling In Afsupporting
confidence: 63%
See 2 more Smart Citations
“…Similar reduction in RA voltage with increased low voltage areas have also been seen in a clinical study involving human patients with long standing PH 25 . Findings from another prospective observational study also suggested that structural RA changes might play a role in AF recurrence in n = 168 AF patients with normal sized LA (defined as diameter < 40 mm) who have undergone a pulmonary vein isolation procedure 26 . In this study by Yano et al, 26 severe tricuspid regurgitation along with a high B‐natriuretic peptide (BNP) were identified as independent predictors of AF recurrence post PVI in this group of AF patients with normal sized LA 26 .…”
Section: Role Of Right Atrial Structural Remodeling In Afsupporting
confidence: 63%
“…In this study by Yano et al, 26 severe tricuspid regurgitation along with a high B‐natriuretic peptide (BNP) were identified as independent predictors of AF recurrence post PVI in this group of AF patients with normal sized LA 26 . In addition, nonpulmonary vein triggers originating mainly from the superior vena cava, crista terminalis, coronary sinus ostium and RA septum were also seen more commonly in this subset of patients 26 . Given these findings, there might be a role for right sided atrial substrate modification in patients with extensive right sided atrial remodeling and fibrosis, although no randomized clinical studies have been performed so far to date investigate this hypothesis.…”
Section: Role Of Right Atrial Structural Remodeling In Afmentioning
confidence: 78%
See 1 more Smart Citation
“…However, some patients with PAF who have a standard LA diameter also have a high recurrence rate following ablation. [24][25][26] Electrical remodelling may play a significant role in these patients. The present authors believe that CSNRT is a marker for both electrical and structural remodelling of the atrium, and is an important supplement to LAVI for predicting AF recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In this direction, one step has just been attempted in the study performed by Masamichi et al 2 In this study, the investigators hypothesized that patients had "normal" left atrium if the left atrial diameter was not larger than 40 mm. In this special group of patients, they analyzed the electrophysiological and clinical characteristics in the recurrent patients after CPVI.…”
mentioning
confidence: 99%